Screening for Both Child Behavior and Social Determinants of Health in Pediatric Primary Care. Issue 6 (July 2019) - Berger-Jenkins, Evelyn; Monk, Catherine; D'Onfro, Katherine; Sultana, Majeda; Brandt, Lisa; Ankam, Jyoti; Vazquez, Nadiuska; Lane, Mariellen; Meyer, Dodi
ABSTRACT: Objective: To implement comprehensive screening for child behavior and social determinants of health in an urban pediatric practice and explore rates of referrals and follow-up for positive screens. Method: Quality improvement methodology was used to implement routine screening using an adapted version of the Survey of Well Being of Young Children, a child behavior and social screen, for all children aged 6 months to 10 years. Rates of screen administration and documentation were assessed for 18 months. Medical records of a convenience sample (N = 349) were reviewed to track referrals and follow-up for positive screens. A secondary analysis explored associations between reported parental concern for their child's behavior and both child behavior symptoms and social stressors. Results: Over 18 months, 2028 screens were administered. Screening rates reached 90% after introducing a tablet for screening. Provider documentation of screens averaged 62%. In the convenience sample, 28% scored positive for a behavioral problem, and 25% reported at least 1 social stressor. Of those with positive child behavior or social stressor screens, approximately 80% followed up with their primary medical doctor, and approximately 50% completed referrals to the clinic social worker. Further analysis indicated that referral and follow-up rates varied depending on whether the family identified child behavior or social issues. Logistic regression revealed that parental concern was independently associated with child behavior symptoms ( p = 0.001) and social stressors ( p = 0.002). Conclusion: Implementing a comprehensive psychosocial screen is feasible in pediatric primary care and may help target referrals to address psychosocial health needs.